Estudo morfométrico e cinético do epitélio jenjunal proximal de ratos com deficiência aguda de tiamina - Cipriano, Teonas Carvalho (1984)
Thirty male Uistar rats ueighing an average of 50 g uere allocated into three groups of 10 animais: group DT - thiamine-deficient, uas fed a thiarnine-f ree diet and uater ad libitum; group CP - pair-fed control, uas pair-fed uith group DT and received a diet uith all nutrients and uater; group AL - ad libitum control, uas fed a diet uith all nutrients and uater ad libitum. They uere ueighed each tu o. days and the consumption diet and uater recorded. After 19 days on test (beginning of the body ueight loss of group DT) the animais uere sacrificed and small pieces of proximal jejunum uere removed and prepared to study the epithelium through microdissection and parafin inclusion techniques. Before sacrifice the animais uere administered vincristina sulphate i.p. to evaluate the crypt cell production rate. The height of the enterocyte from the middle one- third of villi, the depth of crypts, the length of villi and the cellular populations of crypts and villi uere determined. The results shoued that: 1. The animais of the DT group shoued adipsia from 13th day and anorexia from 15th day of the experiment period; 2. The animais of the DT group started significant body ueight loss from 17th day of the experiment group in comparison to CP and AL; 3. The height of the enterocytes from the middle one-third of villi, the depth of crypts, the length of villi and the celular populations of crypts and villi from DT group uere significantly decreased as compared to CP group; 4. The number of crypts/villus and the crypt cell production rate uere similar uhen comparing DT and CP groups. In summary, rats fed thiamine free diet developed initially adipsia followed by anorexia and finally body ueight loss. The adipsia and the epithelial atrophy observed in deficient rats could be responsible, at least in part, for deficient absorption of nutrients commonly observed in thiamine deprivation. Houever, even with epithelial atrophy, the crypt cell production rate uas maintained in thiamine deficient animais, probably due to the presence of immature villus cells, luminal nutrition and adequate DNA production,,